Research on Fracture Mechanism of Roof Plate and Filling Technology of Working Face Over-air Tunnel - Wang, Mingwei (International Journal of Natural Resources and Environmental Studies, 2024)
For a long time, the faults on both sides of the working face have been the technical problems faced by the coal mining face. Aiming at the situation that both sides of 7509 comprehensive workings in Wuyang coal mine are near to big faults, and through several long and short hollow alleys, the theoretical analysis, numerical simulation and other methods are used to study the fracture mechanism of the roof plate of comprehensive workings in both sides of the faults and the technology of safe and fast hollowing of the workings. Through theoretical calculation and numerical simulation, it is finally determined that the filling strength of 4 MPa is the most suitable. And through the field industrial test, it is proved that the working face can realize rapid, safe and stable mining after filling with ultra-high water material.